(using tables of x- and y-values).
x² - 3= 2x
a. X= -1 or x = 3
C. X = -3 or x = -3
b. x= 2 or x = -3
d.x=1 or x = -1

I need help with this plss

Respuesta :

Answer:

a

Step-by-step explanation:

x² - 3 = 2x ( subtract 2x from both sides )

x² - 2x - 3 = 0 ← in standard form

consider the factors of the constant term (- 3) which sum to give the coefficient of the x- term (- 2)

the factors are - 3 and + 1 , since

- 3 × + 1 = - 3 and - 3 + 1 = - 2 , then

x² - 2x - 3 = (x - 3)(x + 1) = 0 ← in factored form

equate each factor to zero and solve for x

x + 1 = 0 ⇒ x = - 1

x - 3 = 0 ⇒ x = 3